University based interdisciplinary space lab: Designing for astronaut health and wellbeing. (September 2021) - Alexander, Sasha; Bannova, Olga
Abstract: The importance of interdisciplinary approaches through collaborative mindset, cross-field knowledge, and co-creative team actions is integral for continuing space exploration success as evidenced by past and ongoing terrestrial space habitat analog missions and extraordinary International Space Station (ISS) achievements. This paper presents the third annual iterative outcomes of an innovative university-based space program using Project Based Learning (PBL) methodology in creating design ideas for astronaut health support and wellbeing during a long duration mission (LDM) for a future inhabited lunar moon base or Mars Mission astronaut transit. University faculties including Built Environment, Industrial Design, Engineering, Science, and Health, at Western Sydney University Australia and supported by University of Houston USA are brought together to develop a new understanding of discipline capabilities with the prospect to co-creatively provide new opportunities and inspiration for teamwork across fields. This is of key interest to employers of new graduates in space or innovation-based industries where human factors and designing for high quality human-centered outcomes supports career resilience through currency, agility, and focus. The altruistic nature of interactions that make the ISS a success on multiple levels across cultural, scientific and humanitarian foundations provide the template for cross-disciplinary inspiration, that leverage synergies, and shared goals unattainable by single fields alone. It is not common for disciplines to work so closely together though industry has an expectation for this knowledge. Previously teams of three (2018); five (2019), and now ten undergraduates in 2020 represent team formation. Student numbers across the design for space theme have grown annually from fifteen, to twenty-five, to forty students in 2020. Now opportunities to respond to the complexities of the project in more detail are presented in addressing the overarching research domains in spatial design, human factors and design for health for LDMs. Team supervisory academic staff grew from 1-to-3 and provided further team guidance and discipline specialisations to inform three iterative project phases across the twelve activity weeks for four teams focusing on human spaceflight, exercise, related design performance and materials, and selected UNSDGs principles. The paper outlines the methodological approach, assessment methods, acculturation to working in teams and immersion in space knowledge for newcomers, and a review of forty collaborative outcomes all conducted by migrating Online during the COVID19 pandemic of 2020 by necessity. Periodic project collaborations with sports and health science, engineering, health informatics, space architects, a former astronaut, a representative from NASA Johnson Space Center (JSC) Flight Control, and industrial design academics (project host discipline and non-traditional space area) provided an environment for discussion, development, and co-creative processes that have led to new discoveries and stimuli for new collaboration, international understanding and advancing humankind in space and on earth. Highlights: University space curriculum in design for Astronaut health and wellbeing Space Habitat Design Interdisciplinary Project Based Learning Astronaut Health on Long Duration Missions Space Architecture